2017
DOI: 10.25036/jphr.2017.1.1.craighead
|View full text |Cite
|
Sign up to set email alerts
|

Kinesiology Tape Modestly Increases Skin Blood Flow Regardless of Tape Application Technique

Abstract: Background and Purpose: Kinesiology tape (KNT) is commonly used for prevention of injury and as part of rehabilitation to treat muscle and joint pain. KNT is purported to increase local blood flow by reducing local pressure. Whether skin blood flow is increased by KNT is not presently known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It is very important to note that the two methods of application (with tension and without tension) differ significantly in terms of the pressure exerted on the skin. Although skin convolutions are thought to enhance local blood flow, the available data do not strongly support this claim [41][42][43]. While there are various studies of lower back pain that indicate no significant effects or differences between elastic taping applications with or without convolutions [44,45], there is a lack of similar data for the cervical area, except for the research conducted by Ay et al [32].…”
Section: Discussionmentioning
confidence: 99%
“…It is very important to note that the two methods of application (with tension and without tension) differ significantly in terms of the pressure exerted on the skin. Although skin convolutions are thought to enhance local blood flow, the available data do not strongly support this claim [41][42][43]. While there are various studies of lower back pain that indicate no significant effects or differences between elastic taping applications with or without convolutions [44,45], there is a lack of similar data for the cervical area, except for the research conducted by Ay et al [32].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the two methods of application (with tension and without tension) differ significantly in terms of the pressure exerted on the skin. Although skin convolutions are thought to enhance local blood flow, the available data do not strongly support this claim [41][42][43]. While there are various studies on lower back pain that indicate no significant effects or differences between elastic taping applications with or without convolutions [44,45], there is a lack of similar data for the cervical area; except for the research conducted by Ay et al [32].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study did not explore the physiological mechanisms underlying the observed increase in DFA. Previous studies have examined factors such as changes in skin blood flow 22 ) and the excitability of motor neurons 23 ) in relation to elastic tape application; however, these factors were not investigated in this study. In addition, the impact of physiological phenomena represented by the alpha-gamma linkage and the axon reflex on the intraweight muscle should also be considered.…”
Section: Discussionmentioning
confidence: 99%